Mammal community composition and season determine the abundance of questing ticks in mountainous forests of central Japan - Iijima, Hayato; Morishima, Kaori; Komine, Hirotaka; Watari, Yuya; Doi, Kandai; Okabe, Kimiko (International journal for parasitology. Parasites and wildlife, 2025)
Understanding the ecological drivers of tick abundance is crucial to mitigate the growing risk of tick-borne diseases such as severe fever with thrombocytopenia syndrome (SFTS) in Japan. This study investigates how mammal community composition and seasonality affect the abundance of questing ticks in mountainous forests of Gifu Prefecture, a border region of the SFTS endemic zone. Camera traps were used to monitor mammal species, and questing ticks were collected monthly via flagging along transects in 10 forest plots during 2021–2022. We recorded 14 mammal species including small-sized mammals like mice, medium-sized mammals like raccoon dog (Nyctereutes viverrinus), and large-sized mammals like wild boar (Sus scrofa). Among them, sika deer (Cervus nippon) was the most abundant. A total of 408 adult, 292 nymphal, and 1480 larval ticks representing 11 species (five Haemaphysalis species, five Ixodes species, and Amblyomma testudinarium) were collected. Generalized linear mixed models revealed that the abundance of adult Haemaphysalis kitaokai and H. megaspinosa, and nymphal H. flava and H. megaspinosa were significantly associated with sika deer abundance. Seasonal patterns varied by species and life stage, with H. kitaokai adults peaking in spring and early winter, and H. megaspinosa adults and nymphs in autumn. Wild boar abundance did not significantly influence tick numbers. These findings highlight the importance of sika deer as a key host driving tick population dynamics and underscore the role of host-targeted management, particularly deer population control, as a potential strategy to reduce tick density and related disease risks. Long-term monitoring is essential given ongoing climate and land-use changes that may alter tick phenology and distribution. Our results contribute to region-specific understanding of tick ecology and support the development of effective, ecologically informed countermeasures against tick-borne diseases in Japan. [Display omitted] •Sika deer abundance was associated with higher questing tick abundance.•Tick abundance was generally high in spring and autumn but differed among tick species.•Deer population control is suggested as an ecological strategy to reduce tick abundance.